Effect of Transversus abdominis muscle training on pressure-pain threshold in patients with chronic low Back pain - Changming Xu; Zhiwei Fu; Xueqiang Wang (BMC, 2021)
Abstract Background Therapeutic training is the most commonly used treatment methods for chronic low back pain (CLBP), and the use of a pressure biofeedback unit for transversus abdominis muscle (TrA) training is one of the core muscle training methods. The study aim of this research is to explore the effects of different intensities (sham training, low-intensity and high-intensity) of TrA muscle training on people with CLBP in pressure-pain threshold (PPT). Methods A total of 45 patients with CLBP were recruited, of whom 44 were included in the analysis. Fifteen, 14, and 15 were included in the sham training group, the low-intensity group, and the high-intensity group, respectively. A pressure biofeedback unit was used in performing a one-time TrA training intervention involving 30 times of 180 mmHg TrA contraction training at high intensity for 10 min and 15 times of 100 mmHg TrA contraction training at low intensity for 5 min. The sham training group completed comfort exercises and did not undergo training. The evaluation indicators were as follows: PPT, short-form McGill pain questionnaire, and body surface pain radiation. Results High-intensity training could activate more waist core muscles than low-intensity training. Significant changes on PPT (units: kgf) were observed in the following four muscles immediately after high-intensity training: iliopsoas [0.69 (0.13-1.25) 95% CI, p = 0.020]; quadratus lumborum [0.84 (0.23-1.45) 95% CI, p = 0.012]; erector spinae [0.66 (0.18-1.15) 95% CI, p = 0.011]; transversus abdominis [0.70 (0.26-1.14) 95% CI, p = 0.004], and in three muscles after low-intensity training: quadratus lumborum [0.61 (0.17-1.05) 95% CI, p = 0.009]; transversus abdominis [0.14 (from − 0.15 to 0.43) 95% CI, p = 0.022]; piriformis [0.55 (0.13-0.98) 95% CI, p = 0.014]. The change in body surface pain radiation immediately after exercise was [− 10.87 (from − 17.51 to − 4.22) 95% CI, p = 0.003] for high-intensity training and [− 5.21 (from − 9.40 to − 1.03) 95% CI, p = 0.019] for low-intensity training. Conclusions TrA training could increase the PPT of the waist core muscles and reduce the radiation range of waist pain. The benefits of high-intensity training are higher than those of low-intensity training. Trial registration ChiCTR-TRC-13003701 . Registered 18 October 2013. Code of ethical approval: 2018069.